Epistemological and writing beliefs in a first-year college writing course: Exploring shifts across a semester and relationships with argument quality - Neely, Michelle E. (Journal of Writing Research, 2014)
This study examined 164 freshman undergraduates’ epistemological and writing beliefs, and rhetorical writing performance, in a first-year writing course. Students completed epistemological and writing belief scales early and late in the semester. In addition, their end of semester rhetorical writing assignment was collected. Correlational analyses indicated significant relationships between students’ epistemological and writing beliefs across a 16-week semester. Results of MANOVA show a significant shift in students’ epistemological beliefs regarding fast learning and certain knowledge across the semester, as well as significant changes in their view of writing as a product and writing’s purpose to avoid disagreement. Correlational analyses link students’ writing beliefs to their rhetorical writing performance. The study includes a discussion of qualitative features of students’ writing relative to their writing beliefs.